How smallholder farmers adapt to climate change: Stories from India - Anil Kumar-Singh - Kumar-Singh A (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Anil Kumar-Singh is an Indian farmer (Jamnapur, Bihar India) with a family to provide for. He talks about the consequences of the decreasing water level and how the lack of an electrical infrastructure does not allow them to use water pumps and to irrigate the fields. The changing weather is really becoming a problem.